Convenient methods for preparing π-conjugated linkers as building blocks for modular chemistry - Kulhánek, Jiří; Bureš, Filip; Ludwig, Miroslav (Beilstein Journal of Organic Chemistry, 2009)
Simple, straightforward and optimized procedures for preparing extended π-conjugated linkers are described. Either unsubstituted or 4-donor substituted π-linkers bearing a styryl, biphenyl, phenylethenylphenyl, and phenylethynylphenyl π-conjugated backbone are functionalized with boronic pinacol esters as well as with terminal acetylene moieties allowing their further use as building blocks in Suzuki–Miyaura or Sonogashira coupling reactions.
Keywords: boronic acid; donor/acceptor; linker; Sonogashira reaction; property tuning; push-pull; Suzuki–Miyaura reaction